2008
DOI: 10.1007/s00345-008-0251-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of lymphadenectomy in high risk prostate cancer

Abstract: Historically, patients with high risk prostate cancer were considered poor candidates for radical prostatectomy (RP) due to the likelihood of positive pelvic lymph nodes and decreased long term survival. Although there is still no consensus on the optimal therapy for this group of patients, there is increasing evidence that surgery could play a role. Cancer specific survival (CSS) rates after RP for locally advanced disease at 10 year follow up range from 29 to 72%, depending on tumor differentiation. The role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
16
1
Order By: Relevance
“…Burkhard et al also recommended the same method. 17 Although the incidence of postoperative pelvic hematoma in the current study was higher than those reported by other investigators, 14,16 re-drainage was required in only three of the 32 patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Burkhard et al also recommended the same method. 17 Although the incidence of postoperative pelvic hematoma in the current study was higher than those reported by other investigators, 14,16 re-drainage was required in only three of the 32 patients.…”
Section: Discussioncontrasting
confidence: 63%
“…In our series, only one patient had pathological lymph node involvement. This rate (3.9%) of lymph node disease was considerably lower than what is expected (close to 20%) in extended lymph node dissection in high-risk patients (Heidenreich et al, 2007;Burkhard and Studer, 2008). There are several potential explanations for this discrepancy, including lymph node sampling error or inclusion of not truly high-risk patients.…”
Section: Discussionmentioning
confidence: 58%
“…[1][2][3] However, previous reports showed long-term survival of patients with positive lymph nodes after radical prostatectomy. 4,5 Furthermore, meticulous dissection of lymph nodes located in the draining region of the primary tumor-bearing organ is a gold standard procedure for most malignant tumors.…”
Section: Introductionmentioning
confidence: 99%